(untitled) (Economic studies journal, 2021)
Abstract This study aimed to investigate the impact of disclosure of social responsibility on the market value of Jordanian Islamic banks listed on the Amman Stock Exchange. The study followed the descriptive and analytical approach based on the content analysis method for Jordanian Islamic banks, which numbered (3) banks listed on the Amman Stock Exchange during the period (2010-2018); To measure the market value, Tobin’s Q model was used, while an index was used to measure the disclosure of social responsibility as an independent variable. Based on the descriptive analysis and multiple linear regression analysis, the results showed that the largest disclosure of the social responsibility dimensions recorded during the period (2010-2018) was the disclosure of social responsibility towards society at a rate of (52.8%), while the lowest disclosure rate was (20.3 %) Moreover, were to disclose the social responsibility towards employees; the study also revealed that the average market value of Islamic banks during the study period amounted to (1.015). Moreover, the study revealed that there is a statistically significant impact of the dimension of the disclosure of responsibility towards the environment, and after the disclosure towards customers on the market value in the Islamic banks listed on the Amman Stock Exchange, and it disclosed that there is no statistically significant impact of the disclosure of responsibility towards society. After the disclosure of the responsibility towards employees. Finally, the results indicate that there is no statistically significant impact of the disclosure of social responsibility on the market value. These results provide important evidence for the Jordanian supervisory authorities (the Central Bank and others). Therefore, the study recommends that Jordanian Islamic banks be urged and directed to pay more attention to social responsibility. In addition, try to single out a specialized department for it that takes care of its four dimensions (the environmental dimension, the societal dimension, the workers dimension and the customer dimension).